Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Isolation and characterization of an iodide bridged dimeric palladium complex in carbonylation of methanol - Tonde, S. S.; Kelkar, Ashutosh A.; Bhadbhade, Mohan M.; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2005)
Palladium-catalyzed carbonylation of methanol in presence of iodide promoters was investigated. Iodide bridged palladium dimeric complex, [PPh3CH3](2)[Pd2I6] was isolated from the carbonylation reaction mixture and characterized using X-ray crystallography. Reaction mechanism was proposed based on IR and UV spectroscopic characterizations of catalytic species involved in the catalytic cycle. The isolated dimeric palladium species, [Pd2I6](2-) underwent carbonylation to give monomeric species [PdI3CO](-) at atmospheric pressure of carbon monoxide. It was also observed that PPh3 plays an important role to avoid catalyst deactivation at higher temperatures. Turnover frequency (TOF) of 1052 h(-1) was achieved using Pd(OAC)(2)-HI-PPh3 catalyst system at 175 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dirneric palladium; IR spectroscopy; methanol carbonylation; palladium catalyst; reaction mechanism; UV

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Intermolecular benzoyl group transfer reactivity in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate: controlling reactivity by solvate (pseudopolymorph) formation - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2011)
Racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate (rac-3), which usually crystallizes in a monoclinic lattice (Form I, P2(1)/c) from common organic solvents, when crystallized from 2-propanol yielded concomitantly, thin whisker like crystals (Form II, triclinic, P (1) over bar) with inclusion of 2-propanol and water molecules, along with the Form I crystals. Thin fibre-like crystals were also obtained on crystallization from toluene, with inclusion of toluene and water in the crystal lattice (Form III). The Form II and Form III crystals could be converted into the Form I crystals thermally via melt crystallization. Form I crystals exhibit a facile transesterification reaction, but the solvated crystals are unreactive under the same conditions until their transformation to the reactive form. The reactivity patterns of the Form I and Form II crystals correlate well with the molecular organization in them. Since reactivity of the crystals of rac-3 depends on the solvent and the method of crystallization, and the thermal transition of one crystal form to the other, these phase changes can be used as a switch to control the benzoyl transfer reactivity of the constituent molecules in crystals.